Does top managers experience affect firms capital structure? - Tunde, Matemilola Bolaji; Amin Noordin, Bany Ariffin; Wan Ngah, Wan Azman Saini; Md Nassir, Annuar (Elsevier, 2018)
Recently, the importance of traditional firm-specific determinants of capital structure has been challenged. The paper uses the trade-off theory to investigate the managerial experience of top managers as a determinant of capital structure. The paper applies system-generalized method of moments (GMM) which corrects endogeneity problem. Our results reveal that top managers’ experience is positively related to book value measures of capital structure. As top managers’ (CEOs) experience increases, both the book total debt and long-term debt ratios increase. Our results are robust using both the market total debt and long-term debt ratios. Based on the findings, the results suggest that top managers’ experience is a potential determinant of firms’ capital structure. The findings also suggest that experienced top managers maximize the benefits of debt interest tax-shield; top managers can increase firm value.